Yu Yu Hakusho, ghost files. The complete first season [videorecording (DVD)] - Abe, Noriyuki; Cocanougher, Daniel; Watson, Barry (Barry J.) (FUNimation Entertainment, 2008)
"From cutting classes to brawling in the streets, Yusuke Urameshi is not your typical role model. In fact, this kid's nothing more than a fourteen-year-old delinquent with a talent for trouble. But in a single selfless act Yusuke dies while saving another. For such noble sacrifice he is given a second chance at life, but it's to be a life far different than the one left behind. Now a Spirit Detective, the young man must track down demons and humans alike who desire to rule over the three realms of reality"--Container.